The health of adolescents in detention: a global scoping review - Rohan Borschmann, PhD; Emilia Janca, BSc; Annie Carter, BSc; Melissa Willoughby, BA; Nathan Hughes, ProfPhD; Kathryn Snow, PhD; Emily Stockings, PhD; Nicole T M Hill, MBMSc; Jane Hocking, ProfPhD; Alexander Love, MEnv (PH); George C Patton, ProfMD; Susan M Sawyer, ProfMD; et al. (Elsevier, 2020)
Summary: Adolescents detained within the criminal justice system are affected by complex health problems, health-risk behaviours, and high rates of premature death. We did a global synthesis of the evidence regarding the health of this population. We searched Embase, PsycINFO, Education Resources Information Center, PubMed, Web of Science, CINCH, Global Health, the Cochrane Database of Systematic Reviews, the Campbell Library, the National Criminal Justice Reference System Abstract Database, and Google Scholar for peer-reviewed journal articles, including reviews, that reported the prevalence of at least one health outcome (physical, mental, sexual, infectious, and neurocognitive) in adolescents (aged <20 years) in detention, and were published between Jan 1, 1980, and June 30, 2018. The reference lists of published review articles were scrutinised for additional relevant publications. Two reviewers independently screened titles and abstracts, and three reviewed full texts of relevant articles. The protocol for this Review was registered with PROSPERO (CRD42016041392). 245 articles (204 primary research articles and 41 reviews) were included, with most primary research (183 [90%]) done in high-income countries. A high lifetime prevalence of health problems, risks, and conditions was reported in detained adolescents, including mental disorders (0-95%), substance use disorders (22-96%), self-harm (12-65%), neurodevelopmental disabilities (2-47%), infectious diseases (0-34%), and sexual and reproductive conditions (pregnant by age 19 years 20-37%; abnormal cervical screening test result 16%). Various physical and mental health problems and health-risk behaviours are more common among adolescents in detention than among their peers who have not been detained. As the social and structural drivers of poor health overlap somewhat with factors associated with exposure to the criminal justice system, strategies to address these factors could help to reduce both rates of adolescent detention and adolescent health inequalities. Improving the detection of mental and physical disorders, providing appropriate interventions during detention, and optimising transitional health care after release from detention could improve the health outcomes of these vulnerable young people.